2014
DOI: 10.1371/journal.pone.0113346
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of DNA in Carcasses, Slime and Avian Feces May Affect Interpretation of Environmental DNA Data

Abstract: The prevention of non-indigenous aquatic invasive species spreading into new areas is a goal of many resource managers. New techniques have been developed to survey for species that are difficult to capture with conventional gears that involve the detection of their DNA in water samples (eDNA). This technique is currently used to track the invasion of bigheaded carps (silver carp and bighead carp; Hypophthalmichthys molitrix and H. nobilis) in the Chicago Area Waterway System and Upper Mississippi River. In bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
159
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(160 citation statements)
references
References 33 publications
0
159
0
1
Order By: Relevance
“…Positive detections should not necessarily be taken as an indication of presence of live organisms, as DNA could enter the water from other sources, e.g. decaying corpses or bird faeces (Merkes et al 2014; Dunker et al 2016). Before costly management action is taken, ‘ground truthing’ (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Positive detections should not necessarily be taken as an indication of presence of live organisms, as DNA could enter the water from other sources, e.g. decaying corpses or bird faeces (Merkes et al 2014; Dunker et al 2016). Before costly management action is taken, ‘ground truthing’ (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…) via faecal deposition by wide‐ranging predators (Merkes et al . ), transport of carcasses by predators, scavengers or human traffic (e.g. fish that have leapt onto barges and died), or relocation of sediment containing eDNA (e.g.…”
Section: Challenges Of Edna Studies Iii: Confounding Sources Of Ednamentioning
confidence: 99%
“…More recent studies have focused on eDNA with animal origins. Much of this work has focused on aquatic habitats in laboratory (Dejean et al 2011;Thomsen et al 2012b;Goldberg et al 2013;Barnes et al 2014;Strickler et al 2015), while several studies have occurred in aquatic field settings (Thomsen et al 2012a;Merkes et al 2014). Turner et al 2015 presented one of the first comparisons of accumulation of eDNA in open-water versus aquatic sediment samples.…”
Section: Fate: What Factors Influence Edna Persistence?mentioning
confidence: 99%
“…Although feces remains a probable source of eDNA from a wide range of taxa targeted in aquatic (Thomsen et al 2012a) and terrestrial environments (Andersen et al 2012), high rates of success detecting taxa which produce slimy coatings such as amphibians (Ficetola et al 2008) and fish (Jerde et al 2011) suggest that other bodily fluids also act as a source of eDNA. Still other studies have demonstrated that dead carcasses and predator feces may also serve as an eDNA source in some cases (Merkes et al 2014). Although some research has examined the size distribution of eDNA-bearing particles in aquatic environments to provide clues to its possible origins (Turner et al 2014a), we are unaware of any microscopy-based examinations or other studies that directly address the question of what comprises eDNA collected for research and conservation.…”
Section: Introductionmentioning
confidence: 98%